Isatin-benzoazine molecular hybrids as potential antiproliferative agents: synthesis and in vitro pharmacological profiling - Abdel-Aziz HA; Eldehna WM; Keeton AB; Piazza GA; Kadi AA; Attwa MW; Abdelhameed AS; Attia MI (Dove Medical Press, 2017)
Hatem A Abdel-Aziz,1 Wagdy M Eldehna,2 Adam B Keeton,3 Gary A Piazza,3 Adnan A Kadi,4 Mohamed W Attwa,4 Ali S Abdelhameed,4 Mohamed I Attia4,5 1Department of Applied Organic Chemistry, National Research Centre, Giza, 2Department of Pharmaceutical Chemistry, Faculty of Pharmacy, Kafrelsheikh University, Kafrelsheikh, Egypt; 3Department of Oncologic Sciences and Pharmacology, Drug Discovery Research Center, Mitchell Cancer Institute, University of South Alabama, Mobile, AL, USA; 4Department of Pharmaceutical Chemistry, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 5Medicinal and Pharmaceutical Chemistry Department, Pharmaceutical and Drug Industries Research Division, National Research Centre, Giza, Egypt Abstract: In continuation of our endeavor with respect to the development of potent and effective isatin-based anticancer agents, we adopted the molecular hybridization approach to design and synthesize four different sets of isatin-quinazoline (6a–f and 7a–e)/phthalazine (8a–f)/quinoxaline (9a–f) hybrids. The antiproliferative activity of the target hybrids was assessed towards HT-29 (colon), ZR-75 (breast) and A-549 (lung) human cancer cell lines. Hybrids 8b–d emerged as the most active antiproliferative congener in this study. Compound 8c induced apoptosis via increasing caspase 3/7 activity by about 5-fold in the A-549 human cancer cell line. In addition, it exhibited an increase in the G1 phase and a decrease in the S and G2/M phases in the cell cycle effect assay. Furthermore, it displayed an inhibitory concentration 50% value of 9.5 µM against multidrug-resistant NCI-H69AR lung cancer cell line. The hybrid 8c was also subjected to in vitro metabolic investigations through its incubation with rat liver microsomes and analysis of the resulting metabolites with the aid of liquid chromatography-mass spectrometry. Keywords: isatins, hybridization approach, antiproliferative, apoptosis